Core-skin resin particle and preparation method thereof, foam material and composite foam material
By using the structural design and co-extrusion process of core resin particles in electromagnetic shielding materials, combined with the physical foaming process, the problem of existing materials being difficult to combine electrical insulation and efficient electromagnetic shielding is solved, and the lightweight, efficient shielding and low-cost production of the materials are achieved.
Patent Information
- Application Number
- CN202510086566.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing electromagnetic shielding materials are difficult to have electrical insulation characteristics while ensuring high shielding efficiency, and are complex in the process, high cost, and have problems such as high electromagnetic wave reflection and high density.
By using the structural design of core bark resin particles, the core contains a polymer substrate and a conductive masterbatch, and the cortex layer consists of a polymer substrate. It is prepared by coextrusion process to achieve a separate structure between the conductive part and the insulating part, and the foaming structure of the particles is regulated through the physical foaming process to form a porous structure to improve electromagnetic shielding performance.
It achieves the balance between the electrical insulation of the material and the efficient electromagnetic shielding performance, while reducing the density of the material, making the process simple, low cost and easy to industrially produce.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer foaming materials, and specifically relates to core-skin resin particles and a preparation method thereof, a foaming material, and a composite foam material. Background Art
[0002] In recent years, with the rapid development of electronic devices towards high integration and high frequency, the problem of electromagnetic interference (EMI) between electronic components has become increasingly prominent. Therefore, the development of EMI shielding materials has become a current research focus and hotspot. At present, the EMI shielding performance of polymers can be achieved by introducing conductive or magnetic particle fillers. Studies have shown that special distribution / dispersion structures of fillers, such as 3D network structures, isolation structures and foam porous structures, can effectively further enhance EMI shielding capabilities. Among them, the isolation network structure obtained by foaming technology is one of the most promising structures for giving polymer matrices light weight and high EMI shielding properties.
[0003] At present, as the precision and integration of electronic equipment continue to improve, the electromagnetic shielding materials used in electronic equipment must not only ensure high shielding effectiveness, but also have electrical insulation properties. However, excellent EMI shielding performance often requires good conductivity, which is exactly the opposite of electrical insulation properties.
[0004] At present, insulating electromagnetic shielding materials are generally prepared by stacking electromagnetic shielding layers and insulating layers, but this method is complex and expensive. At the same time, most of the prepared insulating electromagnetic shielding materials have the problems of high electromagnetic wave reflection and high density.
[0005] Therefore, developing materials that have both electrical insulation and excellent EMI shielding functions remains an urgent problem to be solved. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a core-skin resin particle and a preparation method thereof, a foaming material, and a composite foam material. The composite foam material has both electrical insulation and electromagnetic shielding controllable functions and has a low density.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a core-skin resin particle, comprising a core and a skin layer, wherein the mass ratio of the core to the skin layer is (80-95):(5-20).
[0009] Preferably, the core comprises a polymer matrix and a conductive masterbatch; the conductive masterbatch comprises a conductive filler, and the mass content of the conductive filler in the conductive masterbatch is 20-45%.
[0010] Preferably, the skin layer comprises a polymer substrate, and the thickness of the skin layer is 5-50 μm.
[0011] Preferably, the aspect ratio of the core-skin resin particles is 1:1 to 3:1.
[0012] Preferably, the conductive filler includes a carbon-based filler and / or a metal filler.
[0013] Preferably, the carbon-based filler includes any one or more of carbon black, carbon nanotubes, graphene nanosheets or expanded graphite; the metal filler includes any one or more of nanosilver particles, silver nanowires or copper powder.
[0014] Preferably, the size of the conductive filler is less than 10 μm.
[0015] Preferably, the conductive filler accounts for 4-20 wt% of the core mass.
[0016] Preferably, the mass of the core-skin resin particles is 0.5-3 mg.
[0017] Preferably, the conductive masterbatch comprises a polymer matrix, a conductive filler and optional auxiliary agents.
[0018] Preferably, the auxiliary agent includes but is not limited to any one or more of an antioxidant, a stabilizer, a lubricant, a nucleating agent, a compatibilizer, a reinforcing agent or a catalyst.
[0019] Preferably, the polymer substrate is selected from any one or more of rubber, thermoplastic resin, degradable resin, engineering plastic or thermoplastic elastomer.
[0020] Preferably, the rubber comprises EVA.
[0021] Preferably, the thermoplastic resin includes any one or more of PP, PE or PS.
[0022] The degradable resin includes any one or more of PLA, PBAT or PPC.
[0023] Preferably, the engineering plastic includes any one or more of PA, PET, PBT, PPO, PES or PEI.
[0024] Preferably, the thermoplastic elastomer includes any one or more of TPU, SEBS, OBC or nylon elastomer.
[0025] Preferably, the conductive masterbatch comprises, by weight, 45 to 89 parts of a polymer matrix, 20 to 45 parts of a conductive filler, and 1 to 10 parts of an auxiliary agent.
[0026] Preferably, the skin layer further comprises a nucleating agent.
[0027] Preferably, in the skin layer, the weight portion of the nucleating agent is 0.3 to 2 parts based on 100 parts of the polymer substrate.
[0028] In a second aspect, the present invention provides a method for preparing the core-skin resin particles, comprising the following steps:
[0029] Mixing a polymer matrix and a conductive masterbatch to obtain a core mixture; mixing a polymer matrix and an optional nucleating agent to obtain a skin material;
[0030] The core mixture and the skin layer material are melt-extruded to obtain core-sheath resin particles.
[0031] In a third aspect, the present invention provides a foaming material, characterized in that it is obtained by physically foaming the core-skin resin particles mentioned above;
[0032] Preferably, the pore diameter of the foaming material is 10-300 μm.
[0033] Preferably, the physical foaming is performed using supercritical carbon dioxide foaming.
[0034] Preferably, the temperature of the physical foaming is 50-300° C., the saturation time is 0.5-2 h, and the saturation pressure is 2-20 MPa.
[0035] In a fourth aspect, the present invention provides a composite foam material, which is obtained by subjecting the above-mentioned foaming material to a molding process.
[0036] Preferably, the molding process is direct molding or pre-pressing followed by molding.
[0037] Preferably, the heat source used in the molding process includes any one or more of steam, hot air or microwaves.
[0038] Preferably, the composite foam material is insulated, has an electromagnetic shielding effectiveness of 20-50 dB, and a density of 30-300 kg / m 3 .
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The present invention provides a core-skin resin particle, comprising a core and a skin layer, wherein the core comprises a polymer matrix and a conductive masterbatch; the conductive masterbatch comprises a conductive filler, and the mass content of the conductive filler in the conductive masterbatch is 20-45%; the skin layer comprises a polymer matrix. The skin layer can form an insulating isolation structure, and the core forms an island structure unit with electromagnetic shielding performance, so that the core-skin resin particle can achieve the goals of electrical insulation and high absorption shielding.
[0041] The present invention adopts a co-extrusion process to prepare core-skin resin particles, selectively distributes the polymer substrate and the conductive filler in the skin layer and the core, and realizes a structural design in which the conductive part is separated from the insulating part. In addition, the core-skin resin particles obtained by the present invention are foamed by a physical foaming process to achieve the purpose of lightweighting the material, and the obtained foamed beads have a porous core structure that improves the electromagnetic shielding absorption characteristics of the material. Furthermore, the present invention can obtain a molded product (i.e., the above-mentioned composite foam material) with a designable shape and both insulation and electromagnetic shielding properties by molding the obtained foamed beads.
[0042] The present invention also provides a method for preparing the above-mentioned composite foam material, which avoids damage to the insulating and thermally conductive network by differentiating macroscopic foam beads into multiple foam particle units, and each unit can maintain an independent structural principle, thereby ensuring that it has excellent electromagnetic shielding performance while having excellent insulation. This method has the advantages of simple process, low cost, no pollution, and easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 It is a schematic diagram of the structure of core-skin resin particles;
[0044] Figure 2 This is a SEM image of the expanded beads obtained in Example 2;
[0045] Figure 3 This is a graph showing the electromagnetic shielding performance of the molded product obtained in Example 2. DETAILED DESCRIPTION
[0046] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] In view of the problems of high conductivity, low absorption, high density, limited application range, and difficulty in preparing complex special-shaped parts of traditional electromagnetic shielding composite materials, the present invention provides a method for preparing a high-strength composite foam material with both electrical insulation and adjustable electromagnetic shielding functions. The preparation method first constructs insulating electromagnetic shielding core-skin resin particles, and then adjusts the electromagnetic shielding performance of the foamed core of the particles by physical foaming. The obtained foamed beads are subjected to molding treatment, the skin layers are bonded to each other to form an insulating isolation structure, and the core forms an island structure unit with electromagnetic shielding performance, ultimately achieving the goals of electrical insulation and high absorption shielding.
[0048] Specifically, the present invention first provides a core-skin resin particle, which includes a core and a skin layer.
[0049] In the present invention, the core includes a polymer matrix and a conductive masterbatch.
[0050] The polymer substrate is a common polymer substrate that can be foamed and extruded. Specifically, the polymer substrate is selected from any one or more of rubber, thermoplastic resin, degradable resin, engineering plastic or thermoplastic elastomer.
[0051] In the present invention, the rubber includes ethylene-vinyl acetate copolymer (abbreviated as: EVA).
[0052] In the present invention, the thermoplastic resin includes any one or more of polypropylene (abbreviated as PP), polyethylene (abbreviated as PE) or polystyrene (abbreviated as PS);
[0053] In the present invention, the degradable resin includes any one or more of polylactic acid (abbreviated as PLA), polybutylene adipate / terephthalate (abbreviated as PBAT) or polypropylene carbonate (abbreviated as PPC).
[0054] In the present invention, the engineering plastic includes any one or more of polyamide (abbreviated as PA), polyethylene terephthalate (abbreviated as PET), polybutylene terephthalate (abbreviated as PBT), polyphenylene ether (abbreviated as PPO), polyether sulfone resin (abbreviated as PES) or polyetherimide (abbreviated as PEI).
[0055] In the present invention, the thermoplastic elastomer includes any one or more of thermoplastic polyurethane elastomer (abbreviated as TPU), SEBS thermoplastic elastomer (abbreviated as SEBS), olefin block copolymer elastomer (abbreviated as OBC) or nylon elastomer.
[0056] In the present invention, the conductive masterbatch includes a conductive filler, and the conductive filler includes a carbon filler and / or a metal filler. The carbon filler includes any one or more of conductive carbon black, carbon nanotubes, graphene nanosheets or expanded graphite, preferably conductive carbon black; the metal filler includes any one or more of nanosilver particles, silver nanowires or copper powder. The carbon filler or metal filler in the present invention preferably has high conductivity, and the size of the filler is preferably less than 10 μm.
[0057] In the present invention, the conductive masterbatch includes a polymer matrix and an optional auxiliary agent in addition to the conductive filler. The meaning of the "optional auxiliary agent" is that the auxiliary agent may be added or not, and the technician can choose it according to the actual system of the polymer matrix and the conductive filler. In the present invention, the auxiliary agent includes but is not limited to any one or more of an antioxidant, a stabilizer, a lubricant, a nucleating agent, a compatibilizer, a reinforcing agent or a catalyst. The present invention has no particular restrictions on the selection and source of the above-mentioned antioxidant, stabilizer, lubricant, nucleating agent, compatibilizer, reinforcing agent or catalyst, and they can be general commercial products commonly used by technicians in the field.
[0058] In some embodiments of the present invention, the conductive masterbatch includes 45-89 parts of polymer matrix, 20-45 parts of conductive filler, and 1-10 parts of auxiliary agent by weight. Preferably, the mass content of the conductive filler in the conductive masterbatch is 20-35%, such as 20%, 22%, 25%, 28%, 30%, 32% or 35%.
[0059] In the present invention, the preparation method of the conductive masterbatch is: preparing the polymer substrate, conductive filler, optional auxiliary agents and other raw materials through the steps of mixing and extrusion granulation, and the preparation process is a general industrial preparation process.
[0060] In some embodiments of the present invention, the polymer matrix and the conductive masterbatch are preferably mixed to obtain a core mixture. The mass content of the conductive filler in the core mixture is 4-20 wt%, such as 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, etc.; preferably 5-15 wt%, so as to ensure that the core has a conductive filler content of 10 wt% after foaming. 2 ~10 4 The surface resistivity of the conductive filler is stable and dissipative, thus showing the electromagnetic shielding effect. If the mass content of the conductive filler is less than 4%, the core after foaming will not show the electromagnetic shielding effect. On the contrary, if it is higher than 20%, the core-skin resin particles will be difficult to foam, and it will easily cause difficulties in the subsequent granulation processing of the particles.
[0061] In the present invention, the skin layer includes a polymer substrate, and the thickness of the skin layer is 5 to 50 μm, preferably 10 to 40 μm. If the skin layer is too thin, it is difficult to ensure the insulation properties of the skin layer. On the contrary, if the skin layer is too thick, the conductive part of the core accounts for a small proportion of the total, and the electromagnetic shielding performance of the foamed material is reduced, making it difficult to meet the overall shielding performance requirements.
[0062] In some preferred embodiments of the present invention, in order to adjust the pore structure of the core layer and the skin layer, a pore nucleating agent is preferably added to the core and the skin layer of the resin particles. The pore nucleating agent can be specifically selected from any one or more of inorganic powders talc, calcium carbonate, silicon dioxide, zinc borate or nano clay. Wherein, the amount of the pore nucleating agent used is controlled to be 0.3 to 2 parts by weight per 100 parts by weight of the polymer substrate, such as 0.3 parts by weight, 0.5 parts by weight, 0.8 parts by weight, 1 part by weight, 1.3 parts by weight, 1.5 parts by weight, 1.8 parts by weight or 2 parts by weight, etc.
[0063] In the present invention, the mass ratio of the core and the skin is (80-95):(5-20), such as 80:20, 83:17, 85:15, 90:10, 93:7 or 95:5, etc., which can ensure that the core has electromagnetic shielding properties while maintaining the appropriate moldability of the subsequent expanded beads and the insulating physical properties of the obtained molded products. The present invention further adjusts the weight ratio of the core and the skin by adjusting the ratio of the feed amount of the core component to the feed amount of the skin component when preparing the core-skin resin particles. The conductivity of the core can be regulated by the addition amount of the conductive masterbatch, and the mass content of the conductive filler in the core is preferably 4-20 wt%, more preferably 5-15 wt%.
[0064] In the present invention, the mass of the prepared core-skin resin particles is 0.5-3 mg, such as 0.5 mg, 1 mg, 1.5 mg, 2 mg, 2.5 mg or 3 mg. The aspect ratio of the core-skin resin particles is 1:1-3:1, such as 1:1, 1.5:1, 2:1, 2.5:1 or 3:1, the length is controlled at 1.5-3 mm, such as 1.5 mm, 1.8 mm, 2 mm, 2.3 mm, 2.5 mm, 2.8 mm or 3 mm, and the diameter is 0.5-1 mm, such as 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1 mm. It should be noted that if the aspect ratio of the core-skin resin particles is less than 1, the core section of the foamed material is large, the insulation is poor, and a complete insulating layer cannot be formed; if the aspect ratio is greater than 3, gaps / holes are easily formed between the particles of the product obtained after the foaming beads are formed, and the apparent quality is poor.
[0065] The present invention also provides a method for preparing the core-skin resin particles, comprising the following steps:
[0066] Mixing a polymer matrix and a conductive masterbatch to obtain a core mixture; mixing a polymer matrix and an optional nucleating agent to obtain a skin material;
[0067] The core mixture and the skin layer material are melt-extruded to obtain core-sheath resin particles.
[0068] In the present invention, the melt extrusion is performed using a co-extruder, and the specific process is a commonly used process in the field.
[0069] The present invention also provides a foaming material, which is obtained by physically foaming the core-skin resin particles to obtain a foaming material with pores, wherein the average diameter of the pores of the foaming material is 10-300 μm.
[0070] In some embodiments of the present invention, the physical foaming is carried out by supercritical carbon dioxide foaming, and then the pressure is quickly released to prepare the foamed beads. The temperature of the physical foaming is 50-300°C, such as 50°C, 100°C, 150°C, 200°C, 250°C or 300°C, etc.; the saturation time is 0.5-2 h, such as 0.5 h, 1 h, 1.5 h, 2 h, etc.; the saturation pressure is 2-20 MPa, such as 2 MPa, 5 MPa, 8 MPa, 10 MPa, 12 MPa, 15 MPa, 18 MPa or 20 MPa, etc.
[0071] In the present invention, the physical foaming process is preferably carried out in a high-pressure closed container device, and the foaming temperature, pressure, and saturation time are selected according to the characteristics of the polymer substrate and can be set according to the conditions reported in the literature. The preferred physical foaming temperature of the present invention is 50-270°C, the saturation time is 0.5-2 h, and the saturation pressure is 2-20 MPa.
[0072] The present invention also provides a composite foam material (also called a "molded product"), which is obtained by subjecting the above-mentioned foamed beads to a molding process; the molding process is performed by direct molding or molding after pre-pressing; the heat source used in the molding process includes any one or more of steam, hot air or microwaves.
[0073] In the present invention, the molding process can adopt common EPS, EPP steam molding equipment or high-pressure steam (0.4~3 MPa) molding equipment, or the foamed beads can be pre-pressed and filled into the mold, and hot air / steam is introduced to form a composite foam material with both insulation and electromagnetic shielding properties.
[0074] In summary, the present invention provides a method for preparing a composite foam material having both insulation and electromagnetic shielding properties, comprising the following steps:
[0075] (1) physically blending the polymer matrix with the conductive masterbatch to obtain composite particles A1; the mass of the conductive filler is 4-20 wt % of the total mass of the composite particles A1;
[0076] (2) melt-extrude the polymer substrate and the composite material particles A1 described in step (1) through a co-extruder to obtain core-skin resin particles having a core conductive layer and a skin insulating layer structure;
[0077] (3) subjecting the core-skin resin particles of step (2) to supercritical carbon dioxide foaming to obtain foamed particles; and subjecting the foamed particles to steam / hot air molding to obtain a composite foam material having both insulation and electromagnetic shielding properties.
[0078] The porous structure of the core after foaming provides electromagnetic shielding and high absorption, and the skin layer molding process can maintain a complete isolation and insulation layer. Therefore, the foam material provided by the present invention provides excellent absorption and shielding efficiency and mechanical properties while ensuring the insulation performance of the composite foam material.
[0079] According to tests, the composite foam material prepared by the present invention using polypropylene as the polymer substrate has insulation properties, an electromagnetic shielding effectiveness of 20-50 dB, and a density of 30-300 kg / m 3 .
[0080] It can be seen that the composite foam material obtained by foaming and molding the core-skin resin particles provided by the present invention has both electrical insulation and adjustable electromagnetic shielding functions and has a low density.
[0081] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.
[0082] The following involves the apparent density of foamed beads and molded products: foamed particles are measured by drainage method; the apparent density of molded products: density = mass / volume, calculated;
[0083] The average cell diameter of the foamed beads was measured and analyzed after obtaining the SEM image using a scanning electron microscope;
[0084] Insulation is measured using a surface resistance tester. When the surface resistance is greater than 10 12 , it means it has insulation properties (indicated by the symbol “◎”);
[0085] The electromagnetic shielding performance was tested using a PAN-x vector network analyzer.
[0086] The following examples and comparative examples all provide a polypropylene molded product, and the preparation method is as follows:
[0087] 1) Preparation of core-skin resin particles: The conductive filler used in preparing the conductive masterbatch CB1 is conductive carbon black, with a particle size range of 20~50 nm and a dibutyl phthalate (DBP) oil absorption of 300~400 mL / 100 g. The conductive masterbatch CB1 includes, by mass fraction: 55% polypropylene resin A, 40% conductive carbon black, and 5% other general additives (3.2% linear low-density polyethylene, 0.5% lubricant erucamide, 0.5% dispersant white oil, 0.5% zinc stearate, and 0.3% antioxidant B215). Polypropylene resin A is selected from propylene-ethylene random copolymer resin (PP, TPC w311). The polypropylene resin A and the conductive masterbatch CB1 are mixed in a suitable ratio to obtain composite particles A1, which are used as the core material. The polypropylene resin A (99.2%), nucleating agent (zinc borate, 0.5%), and antioxidant (B215, 0.3%) are weighed according to the ratio, stirred and mixed at high speed, and the blend is used as the skin layer. The mixture is extruded through a co-extrusion device, and a dual-frequency pelletizer is adjusted to obtain foamed core-skin structure resin particles (the schematic diagram of which is shown in FIG. Figure 1 As shown), wherein the skin layer is an insulating layer and the core is a conductive composite material;
[0088] 2) Preparation of foamed beads:
[0089] Core-skin resin particles (2 kg) and 6 L of water as a dispersion medium are placed in a 10 L autoclave, and 6 g of kaolin as a dispersant, 0.1 g of sodium alkylbenzene sulfonate, and 0.3 g of aluminum sulfate as a dispersant are added. Then, carbon dioxide is injected into the autoclave as a foaming agent according to the required value of the internal pressure (P) of the foaming autoclave. Under stirring, the contents are heated (40-60 min) to the foaming temperature (T) and maintained at the foaming temperature for 20 min. Subsequently, the contents in the autoclave are released to atmospheric pressure together with water to obtain foamed beads;
[0090] 3) Production of molded products:
[0091] The expanded beads were pre-pressed (saturated air pressure 0.15-0.25 MPa), and the expanded beads obtained above were placed in a mold cavity suitable for forming a flat plate with a length of 250 mm, a width of 250 mm, and a thickness of 50 mm, and molded in the mold by steam heating to obtain a plate-shaped foamed molded product. The steam heating molding process was implemented, and the specific method was to apply steam to the mold to obtain a molded product through single-side penetration preheating, double-side penetration heating, and water cooling. The molded product was taken out of the mold cavity and aged in an oven at 80°C for 12 h to obtain a molded product of the expanded beads.
[0092] According to the above method, the present invention prepares corresponding molded products of Examples 1 to 5 and Comparative Examples 1 to 4 in combination with the specific parameters in Table 1 below. The obtained molded products are tested for density, insulation performance and electromagnetic shielding performance. The results are shown in Table 1 (Note: Insulation ◎: Surface resistance>10 12 Ω, antistatic / conductive--: surface resistance ≤10 12 Ω, ----: indicates no electromagnetic shielding).
[0093] Table 1
[0094]
[0095] It can be seen from the data in Table 1 that the molded product obtained after foaming and molding the core-skin resin particles provided by the present invention has excellent insulation and electromagnetic shielding properties and low density.
[0096] It can be seen from Comparative Example 1 that when the mass of the skin layer in the core-skin resin particles is 3 wt%, the insulation of the obtained molded product is significantly reduced. It can be seen that if the mass content of the skin layer is too small, it is difficult to maintain the integrity of the skin layer (i.e., the insulating layer) in the molded product after molding, resulting in the molded product showing antistatic / conductive properties.
[0097] It can be seen from Comparative Example 2 that when the aspect ratio of the expanded beads is 0.7, that is, the diameter of the expanded beads is larger than the length, it is easy to cause more core leakage, which in turn causes the molded product to show antistatic / conductive properties.
[0098] It can be seen from Comparative Example 3 that when the mass content of the conductive masterbatch in the core layer is 15 wt %, the content of the conductive filler becomes lower, so that the molded product after molding cannot show electromagnetic shielding properties.
[0099] It can be seen from Comparative Example 4 that the skin thickness of the expanded beads is 3 μm. It can be seen that the skin is too thin after foaming and the molded product after molding cannot show insulation properties.
[0100] The schematic diagram of the core-skin resin particles obtained in the above-mentioned Example 2 of the present invention is as follows Figure 1 As shown, the black part of the core is the area containing conductive filler.
[0101] The cross-sectional SEM image of the expanded beads obtained in Example 2 of the present invention is as follows: Figure 2 As shown, it can be seen that it has an orderly distributed pore structure.
[0102] The electromagnetic shielding performance test image of the molded product obtained in the above Example 2 of the present invention is as follows: Figure 3 As shown, it can be seen that the electromagnetic shielding performance reaches 25 dB, and its electromagnetic wave shielding is mainly absorption.
[0103] Example 6
[0104] 1) Prepare conductive masterbatch: by mass fraction, including: polyphenylene ether / high impact polystyrene (mass ratio 6 / 4, Bluestar PPO powder LXR040, Secco HIPS 622) alloy 55%, conductive carbon black (particle size range 20~50 nm, dibutyl phthalate (DBP) oil absorption of 300~400 mL / 100 g) 40%, other general additives 5% (linear low density polyethylene 3.2%, lubricant erucamide 0.5%, dispersant white oil 0.5%, zinc stearate 0.5%, antioxidant B215 0.3%). The polymer polyphenylene ether / high impact polystyrene (6 / 4) alloy is physically blended with the above conductive masterbatch to obtain composite particles A1; the mass of the conductive filler (conductive carbon black) is 15 wt% of the total mass of the composite particles A1; the skin material polyphenylene ether / high impact polystyrene (mass ratio: 6 / 4) and the composite material particles A1 are melt-extruded through a co-extruder to obtain core-skin resin particles with a core conductive and skin insulating structure (the core-skin ratio is 90:10, and the skin thickness is 10 μm);
[0105] 2) Place core-skin resin particles (2 kg) and 6 L of water as a dispersion medium into a 10 L autoclave, and add 6 g of kaolin as a dispersant, 0.1 g of sodium alkylbenzene sulfonate, and 0.3 g of aluminum sulfate as a dispersant. Then, according to the internal pressure of the foaming autoclave (15 MPa), carbon dioxide is injected into the autoclave as a foaming agent. Heat the contents (60 min) to the foaming temperature (160 °C) under stirring. o C), and maintaining the foaming temperature for 20 min. Subsequently, the contents in the autoclave are released to atmospheric pressure together with water to obtain foamed beads;
[0106] 3) The foamed beads were steam molded (0.35 MPa) to obtain a material with both insulation and electromagnetic shielding (20 dB) and a density of 0.06 g / cm 3 Polylactic acid foam material.
[0107] Example 7
[0108] 1) Prepare a conductive masterbatch: by mass fraction, including: polylactic acid (NatureWorks, 8052D) 65%, graphite 30%, other general additives 5% (linear low-density polyethylene 3.2%, lubricant erucamide 0.5%, dispersant white oil 0.5%, zinc stearate 0.5%, antioxidant B215 0.3%). Physically blend the polylactic acid with the above conductive masterbatch to obtain composite particles A1; the mass of the conductive filler (graphite) is 18 wt% of the total mass of the composite particles A1; the skin material polylactic acid and the composite material particles A1 are melt-extruded through a co-extruder to obtain core-skin resin particles with a core conductive and skin insulating structure (the core-skin ratio is 95:5, and the skin thickness is 5 μm);
[0109] 2) Place core-skin resin particles (2 kg) and 6 L of water as a dispersion medium into a 10 L autoclave, and add 6 g of kaolin as a dispersant, 0.1 g of sodium alkylbenzene sulfonate, and 0.3 g of aluminum sulfate as a dispersant. Then, according to the internal pressure (6 MPa) of the foaming autoclave, carbon dioxide is injected into the autoclave as a foaming agent. Heat the contents (80 min) to the foaming temperature (160 °C) under stirring. o C), and maintaining the foaming temperature for 10 min. Subsequently, the contents in the autoclave are released to atmospheric pressure together with water to obtain foamed beads;
[0110] 3) The foamed beads were steam molded (0.15 MPa) to obtain a material with both insulation and electromagnetic shielding (30 dB) and a density of 0.06 g / cm 3 Polylactic acid foam material.
[0111] Example 8
[0112] 1) Prepare a conductive masterbatch: by mass fraction, including: polyurethane (Lubrizol, 302EZ) 85%, silver nanowires 10%, other general additives 5% (linear low-density polyethylene 3.2%, lubricant erucamide 0.5%, dispersant white oil 0.5%, zinc stearate 0.5%, antioxidant B215 0.3%). Physically blend the polyurethane with the above conductive masterbatch to obtain composite particles A1; the mass of the conductive filler (silver nanowire) is 5 wt% of the total mass of the composite particles A1; the skin material polyurethane and the above composite material particles A1 are melt-extruded through a co-extruder to obtain core-skin resin particles with a core conductive and skin insulating structure (the core-skin ratio is 96:4, and the skin thickness is 15 μm);
[0113] 2) Place core-skin resin particles (2 kg) and 6 L of water as a dispersion medium into a 10 L autoclave, and add 6 g of kaolin as a dispersant, 0.1 g of sodium alkylbenzene sulfonate, and 0.3 g of aluminum sulfate as a dispersant. Then, according to the internal pressure of the foaming autoclave (12 MPa), carbon dioxide is injected into the autoclave as a foaming agent. Heat the contents (45 min) to the foaming temperature (115 °C) under stirring. o C), and maintaining the foaming temperature for 5 minutes. Subsequently, the contents in the autoclave are released to atmospheric pressure together with water to obtain foamed beads;
[0114] 3) The foam beads are 120 o C steam molding, obtained both insulation and electromagnetic shielding (40 dB), density 0.07g / cm 3 Polyurethane foam material.
[0115] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A core-shell resin particle, characterized in that: It comprises a core and a skin layer, wherein the mass ratio of the core and the skin layer is (80-95):(5-20); The core comprises a polymer substrate and a conductive masterbatch; the conductive masterbatch comprises a conductive filler, and the mass content of the conductive filler in the conductive masterbatch is 20-45%; The skin layer comprises a polymer substrate, and the thickness of the skin layer is 5 to 50 μm; The aspect ratio of the core-skin resin particles is 1:1-3:
1.
2. The core-shell resin particles according to claim 1, characterized in that The conductive filler includes a carbon-based filler and / or a metal filler; The carbon-based filler includes any one or more of carbon black, carbon nanotubes, graphene nanosheets or expanded graphite; the metal filler includes any one or more of nanosilver particles, silver nanowires or copper powder; The size of the conductive filler is less than 10 μm; The conductive filler accounts for 4-20 wt% of the core mass; The mass of the core-skin resin particles is 0.5-3 mg.
3. The core-shell resin particles according to claim 1 or 2, characterized in that: The conductive masterbatch comprises a polymer matrix, a conductive filler and an optional auxiliary agent; The auxiliary agent includes but is not limited to any one or more of an antioxidant, a stabilizer, a lubricant, a nucleating agent, a compatibilizer, a reinforcing agent or a catalyst; The polymer substrate is selected from any one or more of rubber, thermoplastic resin, degradable resin, engineering plastic or thermoplastic elastomer; The rubber includes EVA; The thermoplastic resin includes any one or more of PP, PE or PS; The degradable resin includes any one or more of PLA, PBAT or PPC; The engineering plastics include any one or more of PA, PET, PBT, PPO, PES or PEI; The thermoplastic elastomer includes any one or more of TPU, SEBS, OBC or nylon elastomer.
4. The core-shell resin particles according to claim 3, characterized in that The conductive masterbatch comprises, by weight, 45 to 89 parts of a polymer matrix, 20 to 45 parts of a conductive filler, and 1 to 10 parts of an auxiliary agent.
5. The core-shell resin particles according to any one of claims 1 to 4, characterized in that The skin layer also includes a nucleating agent; In the skin layer, the weight portion of the nucleating agent is 0.3 to 2 parts based on 100 parts of the polymer substrate.
6. A method for preparing core-skin resin particles according to any one of claims 1 to 5, characterized in that: The following steps are involved: Mixing a polymer matrix and a conductive masterbatch to obtain a core mixture; mixing a polymer matrix and an optional nucleating agent to obtain a skin material; The core mixture and the skin layer material are melt-extruded to obtain core-sheath resin particles.
7. A foaming material, characterized in that: Obtained by physically foaming the core-skin resin particles according to any one of claims 1 to 4 or the core-skin resin particles prepared by the preparation method according to claim 5; The average diameter of the pores of the foaming material is 10-300 μm.
8. The foam material according to claim 7, characterized in that: The physical foaming is carried out by supercritical carbon dioxide foaming; The physical foaming temperature is 50-300° C., the saturation time is 0.5-2 h, and the saturation pressure is 2-20 MPa.
9. A composite foam material, characterized in that: Obtained by molding the foaming material according to claim 7 or 8; The molding process is direct molding or pre-pressing followed by molding; The heat source used in the molding process includes any one or more of steam, hot air or microwaves.
10. The composite foam material according to claim 9, characterized in that The composite foam material is insulated, has an electromagnetic shielding effectiveness of 20-50 dB, and a density of 30-300 kg / m 3 .
Citation Information
Patent Citations
Sandwich structure electromagnetic shielding composite foam and preparation method thereof
CN114437396A
Foamed polypropylene bead, preparation method thereof and molded part
CN114907608A
Thermoplastic resin foamed particles and thermoplastic resin foamed particle molded article
CN117467219A
Core-shell type heat-conductive beads, method for producing the same, resin composition, and molded body
JP2020164591A
Electromagnetic wave shield material
JP2021048346A
Cited By
Shrinkage-resistant directional conductive supercritical foaming rubber and preparation method thereof
CN121108640A